Wheat Cooperatives in Morocco: Structure, Governance, Benefits and the Impact of COVID-19 - Najjar, Dina (International Center for Agricultural Research in the Dry Areas, 2023)
presentation on Wheat Cooperatives in Morocco: Structure, Governance, Benefits and the Impact of COVID-19.